Indicators of physical and sexual development of adolescent boys, depending on the functional state of the thyroid gland - K. G. Kamalov; S. A. Abusuyev; G. A. Gazimagomedov (Исследования и практика в медицине)
Republic of Dagestan is a region with medium and severe iodine deficiency, which is associated with the development of endemic goiter and subclinical hypothyroidism. Children with goiter with or without it with SG had the worst indicators of physical, psychological and sexual development, tended to chronic somatic pathology.Objective. To examine the connection between the elevated TSH level with indicators of physical and sexual health of boys.Material and methodThere were examined 297 adolescents aged 11-13 years (76 persons) in the beginning of puberty and 14-17 years (221 people) in the middle and the end of puberty. The anthropometric studies of height, weight were conducted, body mass index BMI was calculated, the degree of sexual development: R - pubic body hair, G-degree sexual development, testicular volume by Prader and the size of the penis, index of virilization, level tireotroponogo hormone (TSH) were assessed.Results showed that physical development of boys already in the early stages of dysfunction of the thyroid gland tends to lag behind. This is more evident in the mid to completion of puberty (boys and adolescents 14-17 years of age), secondary sexual characteristics in boys 11-13 years more marked in those with a TSH level of 0.5 to 2.6 IU/l compared with peers with TSH levels from 4.2 to 10.0 IU/l In the subgroup of 14-17 year old boys and teenagers, there is a tendency to the phenomenon of "macroorchidism" beginning at the stage of subclinical hypothyroidism.